1985
DOI: 10.1139/v85-102
|View full text |Cite
|
Sign up to set email alerts
|

Metallophthalocyanine dimers incorporating five-atom covalent bridges

Abstract: Metal-free copper and cobalt(II) binuclear phthalocyanines, in which the two phthalocyanine nuclci are covalently linked through five-atom bridges, have been prepared and characterized. Some new metal-free, copper, cobalt(II), and zinc 2,9,16,23-tetraalkoxyphthalocyanines, some of which are extremely soluble in organic solvents, are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
84
0

Year Published

1988
1988
2004
2004

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 159 publications
(85 citation statements)
references
References 14 publications
1
84
0
Order By: Relevance
“…Virtually all tetrasubstituted phthalocyanines known in the literature (1) exist as a mixture of the four possible isomers, and in the case of substituents at the 2 position are usually referred to as the 2,9,16,23-tetrasubstituted isomer. On the other hand, in a very recent paper, Gaspard and Maillard (9) have succeeded in preparing the pure isomer 2,9,17,24-tetratert-butylphthalocyanine zinc(II), using metallic zinc as the condensing agent.In connection with our studies on multinuclear phthalocyanine (6,7,10) and with the possibility of obtaining one pure isomer of a binuclear phthalocyanine for X-ray diffraction studies, we were interested in exploring synthetic methods of '~uthor to whom correspondence may be addressed.phthalocyanine formation that could give rise exclusively to the 2,9,16,23-tetrasubstituted phthalocyanines as one isomer. In a previous paper we showed that dithioamides do form phthalocyanines with diiminoisoindolines at modest temperatures (1 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Virtually all tetrasubstituted phthalocyanines known in the literature (1) exist as a mixture of the four possible isomers, and in the case of substituents at the 2 position are usually referred to as the 2,9,16,23-tetrasubstituted isomer. On the other hand, in a very recent paper, Gaspard and Maillard (9) have succeeded in preparing the pure isomer 2,9,17,24-tetratert-butylphthalocyanine zinc(II), using metallic zinc as the condensing agent.In connection with our studies on multinuclear phthalocyanine (6,7,10) and with the possibility of obtaining one pure isomer of a binuclear phthalocyanine for X-ray diffraction studies, we were interested in exploring synthetic methods of '~uthor to whom correspondence may be addressed.phthalocyanine formation that could give rise exclusively to the 2,9,16,23-tetrasubstituted phthalocyanines as one isomer. In a previous paper we showed that dithioamides do form phthalocyanines with diiminoisoindolines at modest temperatures (1 1).…”
mentioning
confidence: 99%
“…Most tetrasubstituted phthalocyanines are prepared by self-condensation of a suitable 3 or 4-substituted phthalonitrile or derivative (4,5). For example, the isoindoline of 4-neopentoxyphthalonitrile will, upon condensation, give not only 2,9,16,23-tetraneopentoxyphthalocyanine (1) but also the 2,10,16,24-, 2,9,17,24-, and 2,9,16,24-tetraneopentoxyphthalocyanine isomers (6,7). Indeed, we have shown that the 2,9,16,23-tetraneopentoxy hthalocyanine zinc(11) (2) derivative exhibited P peaks in its H nmr spectrum, indicating the presence of seven of the possible eight environments collectively present in the four isomers (7).…”
mentioning
confidence: 99%
“…The synthesis of sy.mmetrical tetra [3][4][5][6], oct^ 17-91, and even hexadecaphthalocyanine (Pcs) [10][11][12] are relatively straightforward using an appropriately substituted phthalonitrile as the sole precursor. In most examples these phthalonitrile precursors consist of phthalonitriles containing only one substituent at the 3-or 4-position or disubstituted phthalonitriles having two identical substituent$ on the 4,5-or 3,6-positions, but in one unusual example at the 3,4-position [3].…”
Section: Introductionmentioning
confidence: 99%
“…In most examples these phthalonitrile precursors consist of phthalonitriles containing only one substituent at the 3-or 4-position or disubstituted phthalonitriles having two identical substituent$ on the 4,5-or 3,6-positions, but in one unusual example at the 3,4-position [3]. For S-p-fert butylphenoxy -3,4,6-triff uorophthalo_ nitrile (6), Following the procedure described for g below, but using 3,4,5,6- 3,4,6-trifl uoro-5-p-methylphenoxyphthalonitrile (7). Following the procedure described for 8 below, but using 3j, 5,6-tetrafluorophthalonitrile (l), and p-methylphenol (4), a product was obtained which was chromatographed on flash grade silica gel using ethyl acetate I hexane (l:l) 3,4,6-trichloro-5-p.methylphenoxyphthalonitrile (9).…”
Section: Introductionmentioning
confidence: 99%
“…The great solubility of some tetrasubstituted phthalocyanines results not only from the steric bulk of the substituents preventing aggregation, but also from the presence of the very similar isomers [18,19]. Thus, a mixture of similar isomers may practically be more useful than a single, less soluble isomer [20].…”
Section: Introductionmentioning
confidence: 99%